(untitled) (Machine : Jurnal Teknik Mesin, 2022)
The air blast freezer has been used as a freezing method in fish processing units before being frozen for a long time in cold storage. For this reason, the use of hydrocarbon refrigerants that are more environmental friendly has become a demand and a central issue in the future. This paper presents a theoretical performance study of the use of R290 and R600a as a drop-in replacement to R404A and R507A. The theoretical performance of the system is based on the evaporation temperature variation using CoolPack software with the condensation temperature maintained constant. The important quantities analyzed are mass flow rate, pressure ratio, temperature discharge, heat rejected, power consumption, coefficient of performance, refrigeration efficiency, and energy consumption. The results show that at minimum evaporation temperature, system performance using R290 and R600a is on average ± 14% higher compared to R404A and R507A. R290 has characteristics that are closer to R404A and R507A so it is more suitable to replace the two refrigerants compared to R600a. However, this is a theoretical analysis of the system which can lead to higher performance than normal conditions.